The effect of eccentric and concentric loading speed on the normal achilles tendon: an in vivo biomechanical study. Issue 2 (20th January 2011) - Sweeney, E; Chaudhury, S; Screen, H; Woledge, R; Bader, D; Maffulli, N; Morrissey, D
Abstract : Background: Tendinopathy is a common and disabling condition that can end an athlete's career. Eccentric loading has proven to be an effective treatment measure for tendinopathy. However, current evidence is unclear regarding the optimum speed for eccentric loading. Objectives: To compare the effects of two different speeds of eccentric and concentric loading on Achilles tendon force and muscle activation in healthy volunteers. Methods: Nine healthy volunteers (4 male, 5 female, age range 19–24) performed eccentric and concentric heel raises/drops at two speeds, in a random order. Motion analysis, force plate and electromyography (EMG) data were collected in order to measure Achilles tendon force and muscle activation. Results: The effect of speed on Achilles tendon force was not significant (p=0.74) but the effect of contraction type was significant (p<0.05). There was a significant difference between eccentric and concentric loading on EMG output for gastrocnemius medialis, lateralis and soleus (p<0.001 for all) but there was no significant effect of speed (p=0.05, 0.32, 0.06 respectively). For tibialis anterior and fibularis longus there was a significant effect of speed on EMG (p<0.001 for both) but not of contraction type (p=0.10, 0.30 respectively). Conclusion: There is no effect of speed on Achilles tendon force and the effect of speed on EMG activity is only significant for tibialis anterior and fibularis longus, therefore mechanical challenges to the tendon that are speed dependent are not likely to be due to force magnitude. The differential effects on muscle training may be significant. Further studies in patients are warranted.